2019
DOI: 10.1177/1066896919862618
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1/PD-1 Expression in Endometrial Clear Cell Carcinoma: A Potential Surrogate Marker for Clinical Trials

Abstract: Background. Endometrial clear cell carcinoma (ECCC) represents a rare subtype of endometrial cancer. Recently, immunotherapeutic drugs targeting programmed cell death protein 1 (PD-1)/programmed death ligand-1 (PD-L1) was associated with improved survival in several types of cancer (especially in patients with mismatch-repair (MMR)-deficient status). The aim of this study is to evaluate the correlation between the PD-L1/PD-1 axis and clinical and pathological features in strictly defined ECCC diagnosed at our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…We identified 34 articles studying the prognosis of patients with MMRd tumors in EC [ 25 , 26 , 51 , 54 , 60 , 63 , 70 , 72 , 75 , 76 , 84 , 89 , 92 , 99 , 102 , 105 , 106 , 115 , 120 , 126 , 130 , 131 , 132 , 133 , 135 , 140 , 141 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ]. The studies included an average of 191.5 samples of MMRd tumors (minimum 12, maximum 892).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 34 articles studying the prognosis of patients with MMRd tumors in EC [ 25 , 26 , 51 , 54 , 60 , 63 , 70 , 72 , 75 , 76 , 84 , 89 , 92 , 99 , 102 , 105 , 106 , 115 , 120 , 126 , 130 , 131 , 132 , 133 , 135 , 140 , 141 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ]. The studies included an average of 191.5 samples of MMRd tumors (minimum 12, maximum 892).…”
Section: Resultsmentioning
confidence: 99%
“…MMRd tumors were associated with a lower FIGO stage in three articles [ 92 , 106 , 115 ]; 58% to 90% of low-stage EC were MMRd compared with 41.8% to 78% for MMRp tumors. MMRd tumors were associated with higher FIGO stage in six articles [ 25 , 72 , 132 , 135 , 157 , 160 ]; 58% to 66.7% in higher-stage EC were MMRd compared with 17.6% to 40.6% for MMRp tumors.…”
Section: Resultsmentioning
confidence: 99%
“…This could be translated into practice simply by testing POLE gene mutation, MSI and p53 status [4] . PD-L1 plays an important role in tumour immunology and cancer treatment, and studies have investigated the value of its expression in EC [8] , [9] , [10] .…”
Section: Discussionmentioning
confidence: 99%
“…This has had an active response for patients with gynaecological malignancies. As such, immunotherapeutic strategies need to be developed and established for patients with aggressive EC, including USC [6] , [7] , [8] , [9] . Programmed cell death receptor 1 (PD-1) and its ligand (PD-L1) are playing a progressively important role in tumour immunology and cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the significance of programmed death-ligand 1 (PD-L1) expression in endometrial carcinomas subtypes. 7 , 8 However, the tumoral microenvironment (TME) is complex with different cell lineages, cytokine mediators, and stroma components, and is not limited to the programmed death-ligand axis.…”
Section: Introductionmentioning
confidence: 99%